Gender Differences in Caring for Children with Genetic or Rare Diseases: A Mixed-Methods Study - Shao-Yin Chu; Chin-Chen Wen; Chun-Ying Weng (MDPI AG, 2022)
As a factor in parenting stress, gender differences in caring for children with genetic or rare diseases warrant research attention; therefore, this study explored gender differences in parenting stress, health outcomes, and illness perceptions among caregivers of pediatric genetic or rare disease populations to improve the understanding of such gender differences. Applying a concurrent triangulation mixed-methods design, we conducted a questionnaire survey to assess study measures for 100 family caregivers (42 men and 58 women), which included a free-text response item to probe caregivers' subjective perceptions of the children's illness. The gender differences hypothesis was tested with statistics and the qualitative data about illness perception was analyzed by directed content analysis. Most female caregivers served as the primary caregivers and provided more caregiving, while they experienced significantly increased levels of parenting stress and depressive symptoms compared with male caregivers. Female caregivers perceived the conditions of their children's diseases to be highly symptomatic, with negative consequences and requiring disease control. By contrast, male caregivers had stronger perceptions regarding the negative effects of the disease on the children's quality of life. The gender discrepancy in viewpoints of illness perception sequence may contribute to female caregivers' higher levels of stress and depressive symptoms than males.